The Effectiveness of Problem-Based Learning Model in Improving Higher Order Thinking Skills and Character of Elementary School Students - I Made Sutika; I Made Astra Winaya; Ida Bagus Rai; I Made Sila; I Nengah Sudiarta; I Made Kartika; I Gede Sujana (Jurnal Pendidikan dan Pengajaran, 2022)
Achievement of science learning competence for children in Indonesia is still low. This low achievement is strongly suspected because Indonesian students are not used to dealing with TIMSS and PISA questions. This study aims to analyze the effectiveness of the problem-based learning model to improve higher order thinking skills (HOTS) and the characteristics of elementary students. This study was a quasi-experimental using a non-equivalent control group pretest-posttest experimental design. The experimental class is a class with problem-based learning, while the control class is a class with direct learning. The research population was fifth grade elementary school students. The research sample consisted of 71 students from 5 schools, all of which were public schools. The school sample was determined by stratified random sampling and the class of each school was determined randomly. Data analysis was carried out quantitatively, both descriptively and inferentially. The results of the study show that problem-based learning is better than direct learning to improve HOTS; and problem-based learning is effective for increasing perseverance, responsibility, hard work, cooperation, caring, and tolerance.